a TOXIC FEMININITY IN COLLEEN HOOVER'S UGLY LOVE - Fransisca; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research explores the concept of toxic femininity in Colleen Hoover’s Ugly Love. The data are taken from the novel by Colleen Hoover, entitled Ugly Love, focusing on the character of Tate Collins and how her behaviors reflect internalized patriarchal norms. Drawing upon Kate Manne’s feminist philosophy, particularly her notion of human giver syndrome and misogyny, the analysis identifies key traits of toxic femininity portrayed by Tate, such as emotional self-sacrifice, dependency, and the endurance of emotional pain. The research adopts a qualitative method and uses feminist literary criticism approach to dissect the psychological and relational consequences of these behaviors. By examining Tate's emotional responses and choices, the research reveals how her submission to traditional gender expectations creates a deeply unbalanced and harmful romantic dynamic with Miles Archer. The analysis is divided into two main parts: the first identifies the elements of toxic femininity within Tate’s character, and the second explores the impact of these traits on her relationship. The findings demonstrate that Tate’s toxic femininity results in the creation of a toxic relationship, the reinforcement of patriarchal gender norms, and the inhibition of emotional healing for both herself and Miles. By internalizing the belief that femininity is defined by emotional labor and sacrifice, Tate becomes both the victim and the enabler of her emotional suffering. This research highlights how literary narratives reflect real-world gender ideologies and underscores the necessity of rethinking how female characters are shaped by and contribute to harmful relational dynamics. Keywords: emotional sacrifice and suffering, human giver syndrome, patriarchy, toxic femininity.